Students' perception of social entrepreneurship - Kireeva, Natalya Sergeevna; Zavyalov, Dmitriy Vadimovich; Saginova, Olga Vitalievna; Zavyalova, Nadezhda Borisovna (Revista de la Universidad del Zulia, 2019)
The paper presents the results of an online survey among students of Russian universities. This survey showed that only 34.8% of respondents are familiar with the phenomenon of social entrepreneurship, but the essence of social entrepreneurship is clear to everyone. Sources of information on social entrepreneurship are identified; the author's interpretation of the concept is given.